Heptamethine Cyanine Dye-Doped Single-Walled Carbon Nanotube Electrodes for Improving Performance of HTL-Free Perovskite Solar Cells - Man-Ge Cai; Arina Watanabe; Zhenyu Xu; Yong-Chang Zhai; Achmad Syarif Hidayat; Naoki Ueoka; Miftakhul Huda; Kimitaka Higuchi; Esko I. Kauppinen; Kazumasa Funabiki; Yutaka Matsuo (Molecules)
Perovskite solar cell (PSC) technology holds great promise with continuously improving power conversion efficiency; however, the use of metal electrodes hinders its commercialization and the development of tandem designs. Although single-walled carbon nanotubes (SWCNTs), as one-dimensional materials, have the potential to replace metal electrodes in PSCs, their poor conductivity still limits their application. In this study, the near-infrared (NIR)-absorbing anionic heptamethine cyanine dye-doped SWCNTs functioned in a dual role as an efficient charge-selective layer and electrode in PSCs. Benefiting from the improvement in conductivities and matched energy level of doped-SWCNT, the dual-role SWCNT electrodes applied to PSCs achieved a better performance than the undoped PSCs with a higher short circuit current (JSC) and fill factor (FF).